TbUTP10, a protein involved in early stages of pre-18S rRNA processing in Trypanosoma brucei - Faktorová, Drahomíra; Bär, Anita; Hashimi, Hassan; McKenney, Katherine; Horák, Aleš; Schnaufer, Achim; Rubio, Mary Anne T; Alfonzo, Juan D; Lukeš, Julius (Molecular and biochemical parasitology, 2018)
Ribosome biosynthesis, best studied in opisthokonts, is a highly complex process involving numerous protein and RNA factors. Yet, very little is known about the early stages of pre-18S rRNA processing even in these model organisms, let alone the conservation of this mechanism in other eukaryotes. Here we extend our knowledge of this process by identifying and characterizing the essential protein TbUTP10, a homolog of yeast U3 small nucleolar RNA-associated protein 10 - UTP10 (HEATR1 in human), in the excavate parasitic protist Trypanosoma brucei. We show that TbUTP10 localizes to the nucleolus and that its ablation by RNAi knock-down in two different T. brucei life cycle stages results in similar phenotypes: a disruption of pre-18S rRNA processing, exemplified by the accumulation of rRNA precursors, a reduction of mature 18S rRNA, and also a decrease in the level of U3 snoRNA. Moreover, polysome profiles of the RNAi-induced knock-down cells show a complete disappearance of the 40S ribosomal subunit, and a prominent accumulation of the 60S large ribosomal subunit, reflecting impaired ribosome assembly. Thus, TbUTP10 is an important protein in the processing of 18S rRNA.
Keywords: posttranskripční úpravy RNA; umlčování genů; RNA-Binding Proteins; Gene Silencing; Genes, Essential; Protozoan Proteins; RNA ribozomální 18S; malá jadérková RNA; protozoální proteiny; RNA, Small Nucleolar; RNA Processing, Post-Transcriptional; proteiny vázající RNA; RNA, Ribosomal, 18S; Trypanosoma brucei brucei; esenciální geny